Epidemiologia da insônia em inquérito populacional em uma cidade do sul do Brasil - Fantinel, Everton José (2010)
Insomnia is the most common sleep disorder. It affects millions of people constituting a public health problem with social and individual consequences. This study aimed to evaluate the prevalence of insomnia and its association with sociodemographic, behavioral and drug use. We used a cross-sectional population-based sample of 2732 adults aged 20 years or more living in Pelotas, Brazil. The outcome was operationalized by Insomnia Severity Index. Analysis was adjusted by Poisson regression. The prevalence of insomnia was 28.2% (95% CI: 26.2 to 30.3), with an increased likelihood in women, younger, poorer and do not work people. There was an apparent increase in the prevalence of insomnia in the city over the past ten years, with a marked change in age, becoming more prevalent in young than old.